144k views
5 votes
2 points) Sometimes a change of variable can be used to convert a differential equation y′=f(t,y) into a separable equation. One common change of variable technique is as follows. Consider a differential equation of the form y′=f(αt+βy+γ), where α,β, and γ are constants. Use the change of variable z=αt+βy+γ to rewrite the differential equation as a separable equation of the form z′=g(z). Solve the initial value problem y′=(t+y)2−1, y(3)=4.

1 Answer

5 votes


y'=(t+y)^2-1

Substitute
u=t+y, so that
u'=y', and


u'=u^2-1

which is separable as


(u')/(u^2-1)=1

Integrate both sides with respect to
t. For the integral on the left, first split into partial fractions:


\frac{u'}2\left(\frac1{u-1}-\frac1{u+1}\right)=1


\displaystyle\int\frac{u'}2\left(\frac1{u-1}-\frac1{u+1}\right)\,\mathrm dt=\int\mathrm dt


\frac12(\ln|u-1|-\ln|u+1|)=t+C

Solve for
u:


\frac12\ln\left|(u-1)/(u+1)\right|=t+C


\ln\left|1-\frac2{u+1}\right|=2t+C


1-\frac2{u+1}=e^(2t+C)=Ce^(2t)


\frac2{u+1}=1-Ce^(2t)


\frac{u+1}2=\frac1{1-Ce^(2t)}


u=\frac2{1-Ce^(2t)}-1

Replace
u and solve for
y:


t+y=\frac2{1-Ce^(2t)}-1


y=\frac2{1-Ce^(2t)}-1-t

Now use the given initial condition to solve for
C:


y(3)=4\implies4=\frac2{1-Ce^6}-1-3\implies C=\frac3{4e^6}

so that the particular solution is


y=\frac2{1-\frac34e^(2t-6)}-1-t=\boxed{\frac8{4-3e^(2t-6)}-1-t}

User Jose CC
by
5.8k points